Developing The English Teaching Materials on Writing Descriptive Text By Using Pictures Media for Eighth Grade Students of SMP Swasta Marapati - Angelina Wola; Ike Dian Puspita Sari (UIBU, 2022)
This development research uses the Research and Development method or commonly known as R&D. This study also uses the Expository Learning model which focuses on students' ability to write descriptive texts with image media. Therefore, this development research is a form of research that will later produce a product of teaching materials in the form of a module that will be used in learning English on the subject of writing for Eight Class students of SMP Swasta Marapati. The product that has been developed, the researcher chooses a validator in order to determine the level of feasibility of the teaching materials developed. The teaching material products will be validated by three validators, namely; design experts, materials/content experts, and learning practitioners. To find out the extent of the feasibility of the product, the researchers distributed questionnaires or questionnaires to several validators. For Content or Material Validators, they get a score of 72.5%, when viewed from the feasibility score, the teaching materials developed are in the Good category. As for the Learning Design, it gets a score of 70% with a decent score. Then from the learning practitioners from the questionnaire given a score of 85% with a very good predicate.